The Influence of Intellectual Intelligence, Emotional Intteligence, and Spiritual Intelligence on Employee Ethical Behavior - Muchammad Maulana Abdillah; Tuti Hastuti; Soedjono; Dharmayanti Pri Handini (Optima Science, 2023)
The aim of this research is to empirically test the influence of intellectual intelligence, emotional intelligence and spiritual intelligence on the ethical behavior of employees of the Department of Industry and Trade of Pasuruan City. The approach used in this research is quantitative research. The population in this study were all Civil Servants (PNS) of the Pasuruan City Industry and Trade Service, totaling 66 people. The number of samples in the study was determined using a saturated sample, because the population was relatively small (less than 100). The research model used is multiple linear regression using program assistanceIBM SPSS Statistics 25. The research results show that intellectual intelligence can partially improve ethical behavior. Emotional intelligence can partially improve ethical behavior. Spiritual intelligence can partially improve ethical behavior. Intellectual intelligence, emotional intelligence and spiritual intelligence can simultaneously improve ethical behavior. Spiritual intelligence is a dominant factor that can increase ethical behavior.